2023
DOI: 10.1002/rob.22231
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous aerial robotics for package delivery: A technical review

Abstract: Small unmanned aerial vehicles (UAVs) have gained significant interest in the last decade. More specifically these vehicles have the capacity to impact package delivery logistics in a disruptive way. This paper reviews research problems and state‐of‐the‐art solutions that facilitate package delivery. Different aerial manipulators and grippers are listed along with control techniques to address stability issues. Landing on a platform is next discussed which encompasses static and dynamic platforms. Landing on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 273 publications
0
1
0
Order By: Relevance
“…In the fields of unmanned aerial vehicles (UAVs), aerial transportation and manipulation (1)(2)(3)(4)(5)(6) have drawn more attention because they notably extend the capabilities of UAVs (7), where UAV grasping plays a crucial role (8,9). Numerous studies on UAV grasping (10)(11)(12)(13)(14) have been reported to date, including rigid grippers designed to mimic avian claws (15)(16)(17)(18)(19)(20), achieving grasping by establishing precise dynamic models of the entire system (19,21) or installing a series of sensors on the gripper (20).…”
Section: Introductionmentioning
confidence: 99%
“…In the fields of unmanned aerial vehicles (UAVs), aerial transportation and manipulation (1)(2)(3)(4)(5)(6) have drawn more attention because they notably extend the capabilities of UAVs (7), where UAV grasping plays a crucial role (8,9). Numerous studies on UAV grasping (10)(11)(12)(13)(14) have been reported to date, including rigid grippers designed to mimic avian claws (15)(16)(17)(18)(19)(20), achieving grasping by establishing precise dynamic models of the entire system (19,21) or installing a series of sensors on the gripper (20).…”
Section: Introductionmentioning
confidence: 99%